What Constrains Agripreneurship? A Factor Analytical Study of Vegetable Growers in South Odisha - Chandra, Vineeta; Prusty, Ajay Kumar; Padhy, Chitrasena; Raj, Rabindra Kumar; Ray, Soumik (Indian Journal of Extension Education, 2026)
The study analysed the constraints of entrepreneurial behaviour of vegetable growers in South Odisha and identified priority interventions for agripreneurial development. Using an exploratory design, the data collection was carried out from 240 vegetable growers using the structured interview method in 2025. Constraint severity and suggestion priority were calculated with weighted mean scores and ranking, and seven components to explain 100% variance were extracted by P.C.A., with the first three components explaining 57.2%. Results showed that the biggest constraints were untimely availability of inputs (Mean = 2.154), non-sanction of credit required (2.146), low price in market in the presence of market glut (2.079), and inadequate training (2.033). Major supports as suggested by farmers were insurance coverage in bad situations (2.279), organising vegetable growers (2.233). The findings revealed that the performance of agripreneurs is limited by the interlinked market, financial, technology, and institutional factors. Strengthening the coordination of market regulation, flexible credit systems, post-harvest infrastructure, and organisation of farmers is crucial in improving entrepreneurial capacity and the sustainability of income for vegetable growers.